School Well-Being as a Predictor of Student Engagement in SMA Negeri 4 Bone Students - Ramadhani, Lula Muchlisya; Halima, Andi; Jalal, Novita Maulidya (Polteknik Ilmu Pemasyarakatan, 2024)
This study aims to determine the relationship between school well-being and student engagement. The data in this study were 186 subjects of SMA Negeri 4 Bone students, with the sampling method being simple random sampling. Data collection techniques were carried out using a Likert scale with two instruments, namely school well-being with student engagement. The data analysis technique used is the pearson correlation test (pearson product moment correlation). Based on the results of data analysis, the correlation coefficient between school well-being and student engagement is 0.476 with a significance level of 0.001 (p < 0.05). These results indicate that there is a significant positive relationship between school well-being and student engagement in SMA Negeri 4 Bone students.